Implementing the Caregiver Benefit Program in Nova Scotia: Supporting Unpaid Caregivers at Home - Mara Mihailescu (Health Reform Observer - Observatoire des Réformes de Santé, 2021)
Nova Scotia is the only province in Canada to implement the Caregiver Benefit Program, an allowance of $400 a month to eligible caregivers if both the caregiver and care receiver qualify for the program. In response to Nova Scotia's aging population -- a population with increasingly complex chronic conditions -- more attention was given to home care and unpaid caregivers through the Continuing Care Strategy, which set the stage for implementation of more caregiver supports. The goals of the Caregiver Benefit are to acknowledge the contributions of eligible caregivers in providing assistance to a family member or friend, help sustain the support these caregivers provide, and keep people in their homes and out of long-term care. A policy window was created in 2009 for the New Democratic Party (NDP) to implement the Caregiver Benefit quickly after their election win by building on a previous Progressive Conservative initiative, thus fulfilling the NDP's promise to support seniors and caregivers. While no official evaluation has been conducted, it is the role of the Executive Director, Risk Mitigation of the Continuing Care Branch to provide accountability and monitoring of the policy. The Caregiver Benefit helps caregivers feel recognized and supported, however it potentially excludes a vulnerable population of caregivers and does not provide enough support to cover lost wages.